The Monitor project: JW 380 – a 0.26-, 0.15-M⊙, pre-main-sequence eclipsing binary in the Orion nebula cluster - Irwin, Jonathan; Aigrain, Suzanne; Hodgkin, Simon; Stassun, Keivan G.; Hebb, Leslie; Irwin, Mike; Moraux, Estelle; Bouvier, Jerome; Alapini, Aude; Alexander, Richard; Bramich, D. M.; Holtzman, Jon; et al. (Monthly notices of the Royal Astronomical Society, 2007)
We report the discovery of a low-mass (0.26 ± 0.02, 0.15 ± 0.01 M⊙) pre-main-sequence (PMS) eclipsing binary (EB) with a 5.3 d orbital period. JW 380 was detected as part of a high-cadence time-resolved photometric survey (the Monitor project) using the 2.5-m Isaac Newton Telescope and Wide Field Camera for a survey of a single field in the Orion nebula cluster (ONC) region in V and i bands. The star is assigned a 99 per cent membership probability from proper motion measurements, and radial velocity observations indicate a systemic velocity within 1σ of that of the ONC. Modelling of the combined light and radial velocity curves of the system gave stellar radii of for the primary and the secondary, with a significant third light contribution which is also visible as a third peak in the cross-correlation functions used to derive radial velocities. The masses and radii appear to be consistent with stellar models for 2–3 Myr age from several authors, within the present observational errors. These observations probe an important region of mass–radius parameter space, where there are currently only a handful of known PMS EB systems with precise measurements available in the literature.